Improvement in broiler performance by feeding a nutrient-dense diet after a mild feed restriction - Hadaeghi, Mohammad; Avilés-Ramírez, Carmen; Seidavi, Alireza; Asadpour, Leila; Núñez-Sánchez, Nieves; Martínez-Marín, Andrés L. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: The use of early nutrient-restriction programs in broilers can prevent complications such as increased body fat deposition and its consequences. However, feed restriction not always gives the expected results. Objective: To assess the effect of two levels of feed restriction followed by a re-alimentation period with five increasing nutrient levels on growth performance and immune response of broiler chickens. Methods: A total of 330 animals were used. The treatments were: 25 (T25) and 35% (T35) quantitative feed restriction during the starting period, and 0, 2.5, 5, 7.5, 10, and 15% increased energy and protein contents during the growing and finishing periods. Results: For all the T25 treatments, except for T25-0, feed intake (FI) and body weight gain (BWG) were higher, and feed conversion rate (FCR) was lower (p<0.05) compared to the control treatment. In that group, the response of FI and BWG to the increased nutrient density was mostly quadratic (p<0.001), whereas that of FCR was linear (p<0.001). The FI and BWG results were less homogeneous in the T35 treatments, but FCR was lower compared to the control treatment (p<0.05) in all of them. The FCR showed no differences (p>0.05) between treatments during the finishing period. Conclusion: Feeding a nutrient-dense diet after a period of mild feed restriction gives the best results, while increasing nutrient density after a more severe feed restriction does not improve productive results compared to a standard diet. Carcass traits and immune function were not affected by restriction level or nutrient density.